2005
DOI: 10.1155/2005/583406
|View full text |Cite
|
Sign up to set email alerts
|

Cross-sectional study of Hepatitis B Awareness among Chinese and Southeast Asian Canadians in the Vancouver-Richmond community

Abstract: HBV education is necessary in this local Asian community. Programs should target younger, less educated adults and elaborate on the potential serious health consequences of HBV. Vehicles for public education should include the physicians' offices and local media.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

18
59
4

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(81 citation statements)
references
References 8 publications
18
59
4
Order By: Relevance
“…This is in contrast to the Chinese population in Richmond, British Columbia, where increasing age resulted in an increased likelihood of being more knowledgeable (11). Similar to previously published studies in Vancouver (11,17), higher levels of education and fluency in English were associated with more knowledge about hepatitis B. These previous studies assessed patients who were randomly interviewed at a large mall whereas our study interviewed patients who were attending a physician's office.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…This is in contrast to the Chinese population in Richmond, British Columbia, where increasing age resulted in an increased likelihood of being more knowledgeable (11). Similar to previously published studies in Vancouver (11,17), higher levels of education and fluency in English were associated with more knowledge about hepatitis B. These previous studies assessed patients who were randomly interviewed at a large mall whereas our study interviewed patients who were attending a physician's office.…”
Section: Discussionsupporting
confidence: 80%
“…Fourteen questions were used to evaluate patients' knowledge about disease transmission, complications and treatments. Some questions were taken or modified from previously published surveys (11,17,18). Stigmatization was assessed by asking patients if they were ashamed about being chronically infected with hepatitis B and by asking patients if they would share knowledge of their hepatitis B status with friends and family.…”
Section: Questionnaire Administeredmentioning
confidence: 99%
See 1 more Smart Citation
“…34 Some of the previous studies reported that 46.8% of the medical students had understanding on preventive measures such as provision of clean water, improvement in hygiene, restriction to single sex partner, avoidance of transfusion and vaccination (24%, 27%, 6%, 19%, 9%, and 15%), respectively. 50,52 Studies conducted in the general public in India 53 and abroad 54,55 have revealed that the awareness about HBV and Hepatitis B was less. The present study revealed that awareness among the nursing students was better than that among the general public.…”
Section: Discussionmentioning
confidence: 99%
“…The present study showed that there were statistical significant differences between education level and knowledge of the patients in which the higher education level has a higher mean knowledge and practice score regarding HBV and HCV. In many studies, better HBV knowledge has been reported to be significantly associated with the educational level Journal of Rare Disorders: Diagnosis & Therapy ISSN 2380-7245 [28,29], persons provided with knowledge and education have been shown to be more likely to practice preventive measures such as vaccination for HBV and screening for HBV and HCV. In conclusion, the present study showed low prevalence of HBsAg and anti-HCV antibody in patient coming for different types of surgical procedures and dental treatment.…”
Section: Discussionmentioning
confidence: 99%